Glycosaminoglycan and versican deposits in taxane‐induced sclerosis. (1st October 2015) - Okada, K.; Endo, Y.; Miyachi, Y.; Koike, Y.; Kuwatsuka, Y.; Utani, A.
Summary: Docetaxel and paclitaxel are widely used in the treatment of various malignant neoplasms. Taxane‐induced sclerosis is dose‐dependent and usually not generalized. Little information on the pathogenesis of scleroderma is currently available. Here, we report a case of generalized scleroderma and a case of early‐stage oedematous sclerosis, both of which presented with intense versican deposits after administration of taxane for angiosarcoma.